Ang Pag-usbong ng Ginintuang Panahon ng Panulaang Waray (1900 – 1910): Isang Historikal na Pagtimbang sa mga Siday ni Iluminado Lucente (The Rise of the Golden Age of Waray Poetry (1900–1910): A Historical Analysis of the Siday of Iluminado Lucente) - Nibalvos, Ian Mark (Social Sciences and Development Review, 2024)
This paper will understand the content of Iluminado Lucente’s poems, as the great Waray poet, and will interpret the social situation and some factors that drove their creation. This is an attempt to connect the fields of literature and history in creating an image of the Waray in the time and space covered by the study. It is based on the belief that history and literature are streams of experience, events, and awareness of the personality of the people in a particular town or community. To shape the metanarrative of the literary historical relationship, this paper will address three objectives: 1.) describe the development of Waray poetry in the early part of the 20th Century (1900 -1910) by presenting the events that pushed its changes, 2.) to be able to interpret the historical events that can be traced in the writings of Iluminado Lucente that were written during the period covered by the study, and 3.) to be able to explain the significance of the analysis of Lucente’s writings and its connection to the social condition of the period -study the current state of Waray society.